Bútoripari habok komfortelemzése és rugalmasságának vizsgálata - Pongrácz Judit (2015)
In the context of my thesis, I have studied the flexibility, and dealt with the comfort analysis of different foam materials, created by using today’s modern technology. I have applied pressure mapping on all of the foam material before and after exhausting them. Using the data from pressure mapping, I could make a conclusion on the changes in the distribution of the pressure in the studied materials. I have performed the flexibility studies using a certificated machine designed for studying furnitures. With the help ot that machine I simulated sits with a 1300 newton force with a number of repeats (1000, 5000, 10000, 20000). Every time a cycle of simulation was over, I have increased the pressing force by 50 newtons, and measured the sinkage of the foam materials. Using this method I could make conclusions about the change of the flexibility of the foam materials.